2016
DOI: 10.1080/00036846.2016.1167829
|View full text |Cite
|
Sign up to set email alerts
|

Convergence and spillover of house prices in Chinese cities

Abstract: The issue of house price convergence in 34 Chinese cities is investigated. We augmented the convergence model with contemporaneous spatial dependence in house prices and found that price convergence and positive spatial spillover are both present. We explicitly addressed the endogeneity problem by introducing a Bayesian instrumental variable setup, which was estimated with particle filtering techniques. From a growth poles perspective, the empirical evidence indicates that the spread effect in regional house p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 50 publications
1
7
0
1
Order By: Relevance
“…From the perspective of spatial variation, an interesting finding from Table 5 is that probability of spillover transit-in, which is just the negative transit out probability, is decreased along with the direction from southeast to northwest in Beijing. This finding coincides with a fact that the northwest part of Beijing is much more well-developed in terms of the concentration of high-tech industry, educational resources, and the absolute value of housing prices (high); the increasing strength of spillover transit-in is then a reflection of the equalization effect of housing market spillover, as widely discussed in the literature [7].…”
Section: Factors Affecting Spilloversupporting
confidence: 83%
See 1 more Smart Citation
“…From the perspective of spatial variation, an interesting finding from Table 5 is that probability of spillover transit-in, which is just the negative transit out probability, is decreased along with the direction from southeast to northwest in Beijing. This finding coincides with a fact that the northwest part of Beijing is much more well-developed in terms of the concentration of high-tech industry, educational resources, and the absolute value of housing prices (high); the increasing strength of spillover transit-in is then a reflection of the equalization effect of housing market spillover, as widely discussed in the literature [7].…”
Section: Factors Affecting Spilloversupporting
confidence: 83%
“…The externalities and spillover effect in housing markets have attracted growing scholarly interest [1][2][3][4][5][6][7]. Extensive studies have been reported for the housing markets in the developed world [8][9][10][11], while developing countries have also begun to pay attention [7,[12][13][14][15]. Meen [16] provides convincing economic explanations for the driving forces of spillover and summarizes four major mechanisms by which the housing price spillover can occur: migration, equity transfer, spatial arbitrage, and spatial patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Middle-and small-sized cities nurture the most urbanization, and real estate development contributes significantly to urbanization [33,34]. Some studies have separated regional growth dynamics into 'spread' and 'backwash' effects, representing the positive or negative influence of growth in the core city on peripheral cities, respectively [35,36]. The Yangtze River Delta has been undergoing rapid urbanization.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A leading role in this matter seems to be played by research in the UK and USA (HOLMES, GRIMES 2008;HOLMES et al 2011;KIM, ROUS 2012;MONTAGNOLI, NAGAYASU 2015;HOLMES et al 2019). Moreover, there is a rapid growth in studies on the convergence of regional house prices in China (ZHANG, MORLEY 2014;MENG et al 2015;MAO 2016;CHOW et al 2016). Studies on house price convergence are very often completed by an analysis of the impact of fundamental economic factors on convergence club membership.…”
Section: Introductionmentioning
confidence: 99%